Pendidikan Karakter Berbasis Keluarga - Niken Ristianah (Asosiasi Dosen Tarbiyah STAI Darussalam Nganjuk, 2021)
Character Education is a deliberate attempt or effort to develop virtues that are the main human nature that is good for yourself and the surrounding environment. In the process of character building, family education plays a very important role in the formation and development of children's character. Family is the first environment for the child, a very important environment in shaping the personality pattern of the child, because in the family the child is first taught with values and norms. Planting commendable characters such as honest, courageous, disciplined, responsible, cooperation, friendly, patient, independent, affectionate and caring will be realized when in the family instill and carry out character education early on. This can happen because there is a mutual attitude towards the parents towards the child, and the child will feel neglected, and supported by a close bond between the parent and the child at home